Advances in Selenium and Related Compounds Inhibiting Multi-Organ Fibrosis - Xiao X; Huang G; Yu X; Tan Y (Drug Design, Development and Therapy)
Xixi Xiao,1 Guoquan Huang,2,3 Xinqiao Yu,2 Yong Tan2,3 1The Central Hospital of Enshi Tujia and Miao Autonomous Prefecture, Hubei Minzu University, Enshi, 445000, People’s Republic of China; 2Hubei Selenium and Human Health Institute, The Central Hospital of Enshi Tujia and Miao Autonomous Prefecture, Enshi, 445000, People’s Republic of China; 3Hubei Provincial Key Laboratory of Selenium Resources and Bioapplications, Enshi, 445000, People’s Republic of ChinaCorrespondence: Xinqiao Yu; Yong Tan, Email 1361095717@qq.com; tanyong951018@163.comAbstract: Selenium (Se), a critically essential trace element, plays a crucial role in diverse physiological processes within the human body, such as oxidative stress response, inflammation regulation, apoptosis, and lipid metabolism. Organ fibrosis, a pathological condition caused by various factors, has become a significant global health issue. Numerous studies have demonstrated the substantial impact of Se on fibrotic diseases. This review delves into the latest research advancements in Se and Se-related biological agents for alleviating fibrosis in the heart, liver, lungs, and kidneys, detailing their mechanisms of action within fibrotic pathways. Additionally, the article summa-rizes some of the anti-fibrotic drugs currently in clinical trials for the aforementioned organ fibroses.Keywords: selenium, fibrosis, organ, clinical